Effectiveness of Using Mit App Inventor at STKIP Taman Siswa Bima - Putri, Meirizka Hani; Jannah, Miftahul; Fitriati, Ita; Ridwan, Ridwan (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2024)
Effectiveness of Using Mit App Inventor at STKIP Taman Siswa Bima Media learning must be a bridge between teachers and students so that the learning process can run well and the transfer of knowledge carried out by teachers can be conveyed well. In order for the process of teaching and learning activities to be more effective, learning media is needed as a supporting tool. A physical medium, such as a book, movie, video, etc., is referred to as learning media. In the early history of learning, media was only a tool used by someone to provide explanations about material, learning media can also increase their motivation to learn, and clarify and simplify learning concepts. Choosing learning media is very important because learning media must be appropriate to the conditions and level of students' understanding. Conventional learning media will make students bored with lessons, especially if in class learning only focuses on teachers and books, therefore the learning process that is carried out must be up-to-date and provide good results, that's the kind of learning media that should be used. . The research method used in this research is Quantitative Descriptive. Data collection was carried out by distributing questionnaires to students of the STKIP Taman Siswa information technology education study program. The results of this research indicate that the use of Mit App Inventor in the information technology education study program is effective. The first indicator, namely "Platform Quality" gets a percentage of 75% in the "Effective" category, the second indicator "Student Understanding" gets a percentage of 78% in the "Effective" category, the third indicator "Student Preferences" gets a percentage of 73% in the "Effective" category" and the fourth indicator "Benefits obtained" got a percentage of 79% in the "Effective" category. It can be said that Mit App Inventor has good quality, is easy to understand, can provide good benefits to the learning process and is suitable for use as a learning medium in information technology education study programs.